An orbital angular momentum acoustic metasurface for underwater defect detection. (10th January 2022) - Ma, Qiujun; Lu, Chunyao; Minin, Igor V.; Minin, Oleg V.; Wang, Kangyu; Wu, Dawei
Abstract: Fourier diffraction theorem can rapidly predict scattering characteristics of scatterers. This paper theoretically proposes orbital angular momentum (OAM) to simplify the reference library in the underwater Fourier diffraction theorem. An acoustic metasurface is designed to replace the traditional phased array, meanwhile the underwater defect detection combining OAM and Fourier diffraction theorem is verified in the simulation. This acoustic metasurface has a high signal-to-noise ratio when used for underwater defect detection. Compared with the traditional underwater defect detection method, the underwater defect detection method proposed in this paper has the advantages of simple structure and no reference pattern library.